Transcriptomic analysis reveals novel hub genes associated with astrocyte autophagy in intracerebral hemorrhage - Zheng, Yun; Duan, Chengwei; Yu, Haoyun; Jiang, Guannan; Shen, Haitao; Li, Haiying; Wang, Zongqi; Zhou, Xiaohan; Li, Xiang; He, Mingqing (Frontiers in Aging Neuroscience, 2024)
Introduction Neuroinflammation serves as a critical local defense mechanism against secondary brain injury following intracerebral hemorrhage (ICH), and astrocytes play a prominent role in this process. In this study, we investigated astrocytic changes during the inflammatory state after ICH to identify new targets for improving the inflammatory response. Methods We stimulated mouse astrocytes with lipopolysaccharide (LPS) in vitro and analyzed their transcriptomes via ribonucleic acid sequencing. We created an ICH model in living organisms by injecting autologous blood. Results RNA sequencing revealed that 2,717 genes were differentially expressed in the LPS group compared to those in the saline group, with notable enrichment of the autophagic pathway. By intersecting the 2,717 differentially expressed genes (DEGs) with autophagy-related genes, we identified 36 autophagy-related DEGs and seven hub genes. Previous studies and quantitative reverse transcription-polymerase chain reaction results confirmed the increased expression of phosphatidylinositol 3-kinase catalytic subunit type 3 (Pik3c3), AKT serine/threonine kinase 1 (Akt1), and unc-51 like autophagy activating kinase 2 (Ulk2) in astrocytes after ICH. Transcription factors and target miRNAs were identified for the final three DEGs, and 3-methyladenine and leupeptin were identified as potential therapeutic agents for ICH. Conclusion Our findings suggest that astrocyte autophagy plays a critical role in ICH complexity, and that Pik3c3, Akt1, and Ulk2 may be potential therapeutic targets.